A Parametric Learning and Identification Based Robust Iterative Learning Control for Time Varying Delay Systems. (23rd September 2014) - Zhai, Lun; Tian, Guohui; Li, Yan
Abstract : A parametric learning based robust iterative learning control (ILC) scheme is applied to the time varying delay multiple-input and multiple-output (MIMO) linear systems. The convergence conditions are derived by using the H ∞ and linear matrix inequality (LMI) approaches, and the convergence speed is analyzed as well. A practical identification strategy is applied to optimize the learning laws and to improve the robustness and performance of the control system. Numerical simulations are illustrated to validate the above concepts.